2023
DOI: 10.2188/jea.je20220206
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response Relationships Between Cigarette Smoking and Breast Cancer Risk: A Systematic Review and Meta-analysis

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In conclusion, this longitudinal study confirms the inverse association between active smoking and MBD, probably due to the anti-estrogenic effects of tobacco smoking. However, cigarette smoking was recently defined as a risk factor for BC ( 5 , 6 ), therefore suggesting that the causal biological pathway linking smoking and BC not includes MBD but is probably due to the carcinogenic effects of constituents in tobacco smoke on the breast tissue. Given the important anti-estrogenic effect on MBD and the established carcinogenic effect on breast tissue, it would be interesting to evaluate, in future studies, the effect of the inclusion of information on smoking habits during the lifespan as additional parameter in the main existing BC risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, this longitudinal study confirms the inverse association between active smoking and MBD, probably due to the anti-estrogenic effects of tobacco smoking. However, cigarette smoking was recently defined as a risk factor for BC ( 5 , 6 ), therefore suggesting that the causal biological pathway linking smoking and BC not includes MBD but is probably due to the carcinogenic effects of constituents in tobacco smoke on the breast tissue. Given the important anti-estrogenic effect on MBD and the established carcinogenic effect on breast tissue, it would be interesting to evaluate, in future studies, the effect of the inclusion of information on smoking habits during the lifespan as additional parameter in the main existing BC risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2012 monograph 100E on Personal Habits and Indoor Combustions, the International Agency for Research on Cancer (IARC) concluded that there was a direct association between tobacco smoking and female BC risk ( 5 ). Subsequently, a recent review and meta-analysis conducted on the basis of 169 studies, provided further evidence of the causal role of tobacco smoke on the risk of BC, with an increased risk of 7%, 8% and 9% respectively in current smokers, former smokers and ever smokers, compared to non-smokers ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have also con rmed that smoking can increase the risk of female breast cancer and is a controllable risk factor for female breast cancer [12][13][14] . Lai et al found that current smoking status was signi cantly associated with an increased risk of overall and cancer-speci c death in women with breast cancer [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our selection of diseases, although conservative, still accounts for a substantial proportion, approximately 85%, of the global deaths attributed to tobacco smoking as calculated by the Global Burden of Disease Study 26 , suggesting that we have captured a substantial, albeit not wholly exhaustive, proportion of the total hospitalizations attributable to smoking. Despite this, our analysis did not encompass several common and costly diseases that have been demonstrated to be linked to smoking, such as breast and colorectal cancer 21 , 27 , 28 , which stand as the two most frequently diagnosed cancers in Italy 29 . We also did not include diabetes, prostate cancer, and liver cancer, all established to be linked with smoking 21 .…”
Section: Discussionmentioning
confidence: 99%